2017
DOI: 10.1038/s41598-017-00298-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of neural stem cells originating from umbilical cord-derived mesenchymal stem cells in diabetic retinopathy

Abstract: The aim of this study was to evaluate the effects of intravitreal injection of neural stem cells (NSCs) originating from human umbilical cord-derived mesenchymal stem cells (UC-MSCs) on neurodegeneration of diabetic retinopathy (DR) in rats. UC-MSCs were isolated and passaged, followed by induction to NSCs in neural differentiation medium. Four weeks following NSC transplantation, treatment attenuated retinal vascular dysfunction compared with non-treated rats, and BDNF and Thy-1 expression was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 25 publications
1
65
2
Order By: Relevance
“…The decrease in lipofuscin volume can also be explained by the increase in RPE phagocytosis functions. Previous work has also found that many retinal disorders such as diabetic retinopathy, retinal vein occlusion and age-related macular degeneration have low-grade inflammation in their etiopathogenesis [27,28,56,72].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The decrease in lipofuscin volume can also be explained by the increase in RPE phagocytosis functions. Previous work has also found that many retinal disorders such as diabetic retinopathy, retinal vein occlusion and age-related macular degeneration have low-grade inflammation in their etiopathogenesis [27,28,56,72].…”
Section: Discussionmentioning
confidence: 98%
“…WJ-MSCs are hypoimmunogenic and have significant immunomodulatory properties. WJ-MSCs have been shown to suppress chronic inflammation and prevent apoptosis in animal models of neurodegenerative and ischemic retinal disorders [27,28]. WJ-MSCs also stimulate progenitor cells in the retina and elicit selfrepair mechanisms [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal Stem Cells (MSCs) belong to the subtype of stromal cells which have the capacity for self-renewal as well as differentiation into multiple lineages [40]. They are derived from various tissues like umbilical tissue, embryonic mesoderm, bone marrow, adipose tissue, endometrial polyps [40,41]. MSCs have the ability to clone into adherent fibroblast cells possessing unique cell surface receptors [41].…”
Section: Role Of Mesenchymal Stem Cells To Treat Retinal Disordersmentioning
confidence: 99%
“…They are derived from various tissues like umbilical tissue, embryonic mesoderm, bone marrow, adipose tissue, endometrial polyps [40,41]. MSCs have the ability to clone into adherent fibroblast cells possessing unique cell surface receptors [41]. MSCs can differentiate into endoderm, mesoderm and ectoderm; under regulatory control of various transcription factors.…”
Section: Role Of Mesenchymal Stem Cells To Treat Retinal Disordersmentioning
confidence: 99%
“…Since then, the application of eye drops derived from AS (UCB serum, UCBS) or allogeneic serum (allo-S) to treat a wide range of ocular surface diseases, mainly severe dry eye due to either Sjögren syndrome (SS) or ocular graft-versus-host disease (oGVHD), has been explored [3][4][5][6][7]. More recently, stem cells obtained from different sources, including UCB, have been used in cell replacement therapies for a variety of ocular pathologies (ranging from corneal scar to optic nerve degeneration) that are traditionally characterized by poor outcomes when treated with conventional therapies [8][9][10][11][12][13][14][15][16][17]. In the present review, we summarize the various types of products obtained from UCB and their current indications for the treatment of ocular diseases.…”
Section: Introductionmentioning
confidence: 99%